Iron overload thalassemic cardiomyopathy: Iron status assessment and mechanisms of mechanical and electrical disturbance due to iron toxicity - Suree Lekawanvijit (2018)
Patients with thalassemia major have inevitably suffered from complications of the disease, due to iron overload. Among such complications, cardiomyopathy is the leading cause of morbidity and mortality (63.6% to 71%). The major causes of death in this group of patients are congestive heart failure and fatal cardiac tachyarrhythmias leading to sudden cardiac death. The free radical-mediated pathway is the principal mechanism of iron toxicity. The consequent series of events caused by iron overload lead to catastrophic cardiac effects. The authors review the electrophysiological and molecular mechanisms, pathophysiology and correlated clinical insight of heart failure and arrhythmias in iron overload thalassemic cardiomyopathy. © 2009 Pulsus Group Inc. All rights reserved.